Plan de negocios para la creación de una microempresa promotora de eventos institucionales en la ciudad de Quevedo AÑO 2013 - Vite Manzo, Luis Antonio (2014)
This project provides solution to companies when designing and organizing social events, sports, product launches activations, training etc. This project presents a business plan to launch a company Organizing Events, who will take care of every detail in the design, coordination and control of an event. The city of Quevedo lacks specialized advertising agencies in brand activation and impulsaciones that meet the needs of companies with high added value. The company “BTL- PROMOTIONS " Marketing and advertising services sell their services to the business people of the province of Los Rios ,domiciled in the city of Quevedo, Quevedo at the mall shopping center. A total investment of USD $ 70,396.23 is required. The total expenditures for the first year is USD $ 77,918.28 while total income for the first year is U.S. $ 174,096 net income is $ 65,324.94. Understood as a totally viable project